PREVENTING VIOLENCE CRIMES (KIDNAPPING, ARMED ROBBERY, BRIGANDAGE OR COMMUNITY MASSACRE) WITH DRONES: AN EFFECTIVE ALTERNATIVE TO VEHICULAR PATROLS IN NIGERIA - BABALOLA SUNDAY EMMANUEL (International Studies Journal)
Security is a vital component of any Nation’s growth and development, with its absence, there is no progress. Insecurity in Nigeria now has posed significant challenges to the nation's security forces. The study examined prevention of violent crimes with drones as an effective alternative to vehicular patrols in Nigeria. The specific objectives were to determine the impact of drones in the prevention of kidnapping, armed robbery, and communal killings in Nigeria. Three research questions and hypotheses guided the study. The study population was made of 114 officers drawn from Nigeria Police College while a sample size of 89 officers was selected for the study. Descriptive statistics was used to answer the research questions while R2 value Regression analysis was applied to test the hypotheses of the study at a 0.05 level of significance. The result of the study showed that drones have a significant impact on the prevention of kidnappings, armed robbery, communal killings, and other crimes in Nigeria. Recommendations proffered include the need for strategic deployment of drones in all security formations in the country, adequate budgetary provision training of manpower, comprehensive monitoring, and adequate assessment and action on information and intelligence received from drones. This study has identified use of technological devices like drones would help security agencies in the country to be more proactive on issues of insecurity. The study advocates the usage of drones by all security agencies for effective mapping systems in fighting insurgency and other forms of insecurity in Nigeria. Therefore, this study tends to create illumination of the need to safeguard our society with modern technological devices like drones against criminals, because drone usage has been identified as the most effective intelligence gathering and security monitoring.